The imperative to write : destitutions of the sublime in Kafka, Blanchot, and Beckett - Fort, Jeff, 1966- (Fordham University Press, 2014)
Is writing haunted by a categorical imperative? Does the Kantian sublime continue to shape the writer's vocation, even for twentieth-century authors? What precise shape, form, or figure does this residue of sublimity take in the fictions that follow from itand that leave it in ruins? This book explores these questions through readings of three authors who bear witness to an ambiguous exigency: writing as a demanding and exclusive task, at odds with life, but also a mere compulsion, a drive without end or reason, even a kind of torture. If Kafka, Blanchot, and Beckett mimic a sublime vocation i.